Composition of High Molecular Weight Glutenin Subunits in Polish Common Wheat Cultivars (Triticum aestivum L.) - Ewa Filip (Journal of Food Quality)
The main goal of our study was to present research data on genes encoding high molecular weight glutenin subunits (HMW-GS) associated with high flour bread-making quality. This is the leading research objective in our institute in the area of wheat gluten in cultivars that have not been studied so far in that respect, but which can potentially be a valuable source of new information. Identification and characterization of high molecular weight glutenin subunits (HMW-GS) were performed using sequencing and SDS-PAGE and STS-PCR methods. Genes located in the vicinity of the Glu-1 locus have been identified and characterized in 28 Polish cultivars of Triticum aestivum. The results were then analyzed using the following computer programs: Finch TV, BLAST, MEGA 4, Molecular Imager® Gel Doc™ XR, and Quantity One software (Bio-Rad). Three alleles (a, b, c) have been identified in the Glu-A1 locus, 6 alleles (a, b, c, d, e, k) in the Glu-B1 locus, and 2 alleles (a, d) in Glu-D1 using the SDS-PAGE method. The amplification of specific HMW-GS sequences generated one product of 450 bp in 1Dx5 in 13 cultivars of old wheat and of 435 bp in 1Dx2 in 15 cultivars. The amplification products of primers for 1Dy10 and 1Dy12 genes were 422 bp and 552 bp in size, respectively.